Willingness to pay for improved rural water supply in Goro-Gutu District of eastern Ethiopia: An application of contingent valuation - Lema, Zelalem; Beyene, F. (2012)
This study employs a contingent valuation method to estimate willingness to pay for improved rural water supply. It provides information on the demand for improved services and the potential for them to be sustainable. The analysis was based on data collected from 132 households using rural water utilities for at least three years. Both binary and ordered probit models were used to examine the determinants of willingness to pay. The estimated mean and median willingness to pay was found to be Birr 6.83 and 5.87 per household per month. Results indicate that households using water purification methods earn better annual income, participated during the early phase of project implementation and are spending more time in collecting water and hence are more likely to pay. Whereas those households with large family members, which use reliable water sources from convenient water points and got higher starting bid values are less likely to pay. This implies the need to take the specific characteristics of rural households and their service level demand into account in planning rural water supply projects, which may contribute to set sound cost recovery system that can sustain the service delivery.